Theoretical Study of Transition Metal Dichalcogenides Compound TiS2 and Their Intercalated Compound CrTiS2 Using Density Functional Theory - Parmar, Vandana B.; Vora, A. M.
The Density Functional Theory (DFT) based computational study is carried out for the transition metal dichalcogenides (TMDCs) compound TiS2 and their intercalated 3d transition metal compound CrTiS2. It is carried through Generalized Gradient Approximation (GGA) through Quantum ESPRESSO environment employing Perdew-Burke-Ernzerhof (PBE) exchange and correlation effect with an ultra-soft pseudopotential. In the present work, the structural optimization and electronic properties like energy band structure, density of states (DOS), partial or projected density of states (PDOS), total density of states (TDOS), Fermi surfaces and charge density are reported. The effect of charge transfer from guest 3d transition metal Cr-atom to self-intercalated compound TiS2 has been observed. While, the energy band structure of CrTiS2 compound is computed in the non-magnetic state. From the energy band structure of said materials, we conclude that the TiS2 compound has an indirect narrow band gap though the CrTiS2 compound has an overlapped band structure. The TiS2 shows a semiconductor or semi-metallic nature while doped compound with guest Cr-atom has a metallic material..
Keywords: Physics